Critique, technology, and innovation: An interview with Darryl Cressman - Penttilä, Lisann; Cressman, Darryl (NOvation — Critical Studies of Innovation, 2025)
Philosopher of technology, Darryl Cressman, is an assistant professor at Maastricht University. Cressman’s work engages with a wide variety of disciplines and approaches, including Science and Technology Studies (STS), media theory, the history and philosophy of science, innovation studies, and critical theory. He is the editor of The Necessity of Critique: Andrew Feenberg & the Philosophy of Technology (2022), a collection which brings together diverse perspectives from various authors to focus on Feenberg’s critique of technology. In this interview, Cressman provides insights into his philosophical roots, approach, and methodology.